2018
DOI: 10.1155/2018/2104343
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Interval Arithmetic for Solving Fully Fuzzy Linear Systems with Trapezoidal Fuzzy Numbers

Abstract: We present a method for solving fully fuzzy linear systems using interval aspects of fuzzy numbers. This new method uses a decomposition technique to convert a fully fuzzy linear system into two types of decomposition in the form of interval matrices. It finds the solution of a fully fuzzy linear system by using interval operations. This new method uses interval arithmetic and two new interval operations ⊖ and ⊘. These new operations, which are inverses of basic interval operations + and ×, will be presented i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…In the following two theorems, we show that operations "⊖" and "⊘" are inverse of operations "+" and "×," respectively [34].…”
Section: Methodsmentioning
confidence: 91%
“…In the following two theorems, we show that operations "⊖" and "⊘" are inverse of operations "+" and "×," respectively [34].…”
Section: Methodsmentioning
confidence: 91%
“…The multiplication of two fuzzy sets could be achieved using interval arithmetic, as follow [54][55][56]:…”
Section: Proposed Fuzzy-based Approachmentioning
confidence: 99%
“…There are many authors have written about developing fuzzy analysis, significantly solving fully fuzzy linear and nonlinear systems. Different methods have been used to solve these two types of fully fuzzy systems, including a method for computing the positive solution of a fully fuzzy linear system (Ezzati et al, 2012); a method used to solve a fully fuzzy linear system via decomposing the symmetric coefficient matrix into two equations systems with the Cholesky method (Senthilkumar and Rajendran, 2011); the Jacobi iteration method for solving a fully fuzzy linear system with fuzzy arithmetic (Marzuki, 2015) and triangular fuzzy number (Megarani et al, 2022); a method for finding a positive solution for an arbitrary fully fuzzy linear system with a one-block matrix (Malkawi et al, 2015a); the singular value decomposition method for solving a fully fuzzy linear system (Marzuki et al, 2018); the Gauss-Seidel method for solving a fully fuzzy linear system via alternative multi-playing triangular fuzzy numbers (Deswita and Mashadi, 2019); the Jacobi, Gauss-Seidel, and SOR iterative methods for solving linear fuzzy systems (Inearat and Qatanani, 2018);a linear programming approach utilizing equality constraints to find non-negative fuzzy numbers (Otadi and Mosleh, 2012); combining interval arithmetic with trapezoidal fuzzy numbers to solve a fully fuzzy linear system (Siahlooei and Fazeli, 2018); using an ST decomposition with trapezoidal fuzzy numbers to solve dual fully fuzzy linear systems via alternative fuzzy algebra (Safitri and Mashadi, 2019), using LU factorizations of coefficient matrices for trapezoidal fuzzy numbers to solve dual fully fuzzy linear systems (Marni et al, 2018); combining QR decomposition with trapezoidal fuzzy numbers (Gemawati et al, 2018); and using an ST decomposition with trapezoidal fuzzy numbers to solve a dual fully fuzzy linear system (Jafarian, 2016). In the case of fully fuzzy linear matrix equations, several studies have identified methods for solving them, including a method that utilizes fully fuzzy Sylvester matrix equations (Daud et al, 2018;Elsayed et al, 2022;He et al, 2018;Malkawi et al, 2015b), and a method that finds fuzzy approximate solutions (Guo and Shang, 2013).…”
Section: Introductionmentioning
confidence: 99%